Feasibility of Integrated Scientific Literacy Assessment Instrument - Khaira, Najmil; Desnita; Sari, Dewi Puspa (Fakultas Tarbiyah dan Ilmu Keguruan, UIN Kiai Haji Achmad Siddiq Jember, 2024)
One of the abilities needed to survive in the global era is scientific literacy. In assessing student’s scientific literacy achievements, assessment instruments are needed as a measuring tool. The survey that was conducted revealed that teachers have not used scientific literacy assessment instruments. This research aims to develop scientific literacy assessment instrument that is integrated with smartphone-based experimental set. The research method used is ADDIE model. The scientific literacy assessment instrument that has been made is carried out validation, reliabity, and prostictive test to students and teachers at SMAN 2 Padang Panjang. The results of the validation test of the assessment instrument include content, construct and language validity. The data obtained was analyzed using the Aiken'V formula to obtain an average value of 0.91. The reliability of the instrument is known from the reliability coefficient value